Overclaim Legal Protection for Consumers Against Overclaiming Skincare Products and Misleading Advertising - Emil Hakim Rusydi Emil; Sutarman Yodo; Ratu Ratna Korompot (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines the legal consequences of overclaiming practices in the digital skincare market and the adequacy of consumer protection mechanisms available to consumers who suffer harm from misleading advertising in Indonesia. The rapid expansion of digital marketplace platforms has created structural conditions in which exaggerated and unsubstantiated product claims proliferate unchecked, generating financial, physical, and emotional harm to consumers who rely on advertised information as the basis for their purchasing decisions. Employing a normative legal research method supported by qualitative descriptive analysis, this study systematically examines applicable statutory provisions, principally the Consumer Protection Act No. 8 of 1999 and BPOM Regulation No. 3 of 2022, alongside relevant legal doctrines including product liability and strict liability theory. The findings reveal that overclaiming constitutes a clear violation of multiple consumer protection provisions, yet enforcement remains structurally constrained by seller anonymity, platform intermediary defenses, and inadequate regulatory monitoring capacity in digital environments. The existing dual framework of preventive and repressive legal protection is normatively sound but practically insufficient to address the scale and sophistication of contemporary overclaiming practices. This study concludes that meaningful consumer protection requires systemic regulatory reform extending accountability across the entire digital promotional chain, directly contributing to SDG 3, SDG 12, and SDG 16.